Children's respiratory health and oxidative potential of PM2.5: the PIAMA birth cohort study. Issue 3 (11th January 2016) - Yang, Aileen; Janssen, Nicole A H; Brunekreef, Bert; Cassee, Flemming R; Hoek, Gerard; Gehring, Ulrike
Abstract : Introduction: The oxidative potential (OP) of particulate matter (PM) has been proposed as a health-relevant metric, but currently few epidemiological studies investigated associations of OP with health. Our main aim was to assess associations of long-term exposure to OP with respiratory health in children. Our second aim was to evaluate whether OP is more consistently associated with respiratory health than PM mass, PM composition or nitrogen dioxide (NO2 ). Methods: For 3701 participants of a prospective birth cohort, annual average concentrations of OP (assessed by spin resonance (OP ESR ) and dithiothreitol assay (OP DTT )), PM with an aerodynamic diameter of less than 2.5 µm (PM2.5 ) mass, NO2, and PM2.5 constituents at the home addresses at birth and at all follow-up addresses were estimated by land-use regression. Repeated questionnaire reports of asthma and hay fever until age 14 years, and measurements of allergic sensitisation, lung function and fractional exhaled nitric oxide at age 12 years were linked with air pollution concentrations. Results: Asthma incidence, prevalence of asthma symptoms and rhinitis were positively associated with OP DTT (adjusted OR (95% CI) per IQR increase in exposure 1.10 (1.01 to 1.20), 1.08 (1.02 to 1.16), 1.15 (1.05 to 1.26), respectively). These associations persisted after adjustment for most co-pollutants. Forced expiratory volume in 1s and forced vital capacity were negatively associated with OP DTT . These associations were sensitive to adjustment for NO2 . Respiratory health was not significantly associated with PM2.5 mass and OP ESR . Conclusions: Respiratory health was more strongly associated with OP DTT than with PM2.5 mass; OP DTT associations with lung function, but not symptoms, were sensitive to adjustment for NO2 .